Debate over secularisation of the marriage law in the Second Polish Republic - Dworas-Kulik, Judyta (Prawo Kanoniczne, 2020)
The legal mosaic inherited from the partitioning states gave rise to dangerous phenomena, legal bigamy above all. Two conflicting political blocs – the secular and the ecclesiastical one – prevented the personal marriage law from being codified in the interwar period, which would have prevented further deterioration of legal chaos gnawing at the ancient foundations of the state, i.e. marriage and family. The aim of this article is to describe – using the historical and legal method – the most important aspects of dispute that emerged when attempts were made to unify marriage law in the lands of the Second Republic, as well as making reference to the arguments of the parties to the dispute concerning the choice of marriage form, jurisdiction in matrimonial cases and the possibility of dissolving a marriage by divorce.